Pelatihan Kewirausahaan Pembuatan Kompos Unggul Dari Seresah Daun Dengan Induksi Inokulum Fungi Pada Mahasiswa Program Studi Bahasa Arab Sekolah Tinggi Ilmu Tarbiyah Darul Fattah Bandar Lampung - Salman Farisi; Bambang Irawan; Suratman; Sutyarso; Hendri Busman (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Compost is the final substance in the fermentation process of piles of waste/plant litter including animal carcasses. The fermentation needs to be accelerated with human assistance. This saprotrophic fungi isolate has the potential to be developed as a compost inoculum in the manufacture of organic fertilizers. Compost induced with fungal inoculum is able to produce organic fertilizer relatively quickly and contains high plant nutrients. The prospect of the need for organic fertilizers is quite high in supporting organic agriculture, so it is necessary to disseminate information on science and technology and training to the public on the manufacture of organic fertilizers by induction of saprotrophic fungi inoculum. In addition, the availability of garden plant litter is abundant and free from chemical residues. The results of this activity showed that there was an increase in the knowledge and understanding of the training participants in making compost from leaf litter. The average increase in the knowledge of the trainees is 25,25 %.